Adsorption isotherm and kinetics for the removal of nitrate from wastewater using chicken feather fiber. Issue 1 (31st December 2022) - Elemile, O O; Akpor, B O; Ibitogbe, E M; Afolabi, Y T; Ajani, D. O
Abstract: Nitrate has been identified as a major source of water pollution and eutrophication. The use of modified chicken feathers (MCFs) as an adsorbent has not been fully explored. The study therefore assessed the use of MCFs for the adsorption of nitrate. Fresh chicken feathers, obtained from a commercial poultry farm, were first hydrolyzed with sodium hydroxide and activated with HCl a q to give modified chicken feathers, MCFs. Experimental constraints were varied in a series of batch tests including concentration, pH, adsorbent dosage and contact time. FTIR was used to monitor the adsorption processes (before and after) of the polluted water. The outcome showed increase in specific surface area and the favorable formation of adsorption sites of MCFs. For the understanding of adsorption mechanism, experimental data were assessed by Langmuir, Freundlich, Temkin and Sips isotherm equations. Pseudo-first and pseudo-second order models were used to evaluate time characteristics of adsorption. The optimum parameters for adsorption are found to be initial ion concentration, initial pH, adsorbent dosage and contact time 300 mg/L, 8, 10 and 480 min, respectively. This study also reveals adsorption fit the chosen isotherm models in the following order: (Sips >Langmuir > Freundlich > Temkin). Sips isotherm having the best fit infers adsorption took place on heterogeneous surface. Pseudo-second-order is suited for explaining nitrate removal based on statistical R 2 coefficient. The use of MCFs as an eco-friendly, cost-effective and renewable bio-sorbent for wastewater treatment is very possible due to its adsorption ability in the removal of nitrate.